Power of Sakdiyah Ma’Ruf in Stand-Up Comedy Through Appraisal Approach - Zahra Rahmi Fatmawati; Setyo Prasiyanto Cahyono (Universitas PGRI Semarang, 2018)
This thesis is entitled “Power of Sakdiyah Ma’ruf in Stand-Up Comedy through Appraisal Approach”. There are two objectives in this study: to describe the Appraisal system of Attitude and to analyze the realization of power in Sakdiyah Ma’ruf stand-up comedy at TEDxUbud on May 2016. The analysis is based on the theory of appraisal by Martin and White (2005) and critical discourse analysis, especially power by Fairclough (1989). The researcher used descriptive qualitative method to describe the realization of Appraisal’s Attitude and power of each utterances of the written transcription of the video of Sakdiyah Ma’ruf’s stand-up comedy. The researcher found that there are 35 Appraisal system of Attitude which consist of 6 affect (17.14%), 13 judgment (37.14%) and 16 appreciation (45.71%). In terms of gradability, there are 2 low-graded of attitude, 15 medium-graded of attitude and 18 high-graded on. The researcher uses the gradability system of attitude to consider the power of the speaker in her stand-up comedy. Sakdiyah use more than 50% of high-graded attitude which means that she shows herself as a powerful person and has higher position than the hearer.